2013
DOI: 10.1001/jamasurg.2013.700
|View full text |Cite
|
Sign up to set email alerts
|

Increased Admission for Alcohol Dependence After Gastric Bypass Surgery Compared With Restrictive Bariatric Surgery

Abstract: Patients who had undergone GBS had more than double the risk of inpatient care for alcohol abuse postoperatively compared with patients undergoing a restrictive procedure, highlighting a need for healthcare professionals to be aware of this for early detection and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
97
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(112 citation statements)
references
References 13 publications
7
97
0
2
Order By: Relevance
“…RYGB surgery is considered a safe procedure [6] that offers significant sustained weight loss with subsequent reduction in comorbid medical conditions such as diabetes mellitus [7], hyperlipidemia, hypertension [8], obstructive sleep apnea [9], cancer in obese women [10]; and improvement in quality of life [11]. However, recent controversial reports of an increased risk of alcoholism following successful RYGB have emerged [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…RYGB surgery is considered a safe procedure [6] that offers significant sustained weight loss with subsequent reduction in comorbid medical conditions such as diabetes mellitus [7], hyperlipidemia, hypertension [8], obstructive sleep apnea [9], cancer in obese women [10]; and improvement in quality of life [11]. However, recent controversial reports of an increased risk of alcoholism following successful RYGB have emerged [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Baseline AUD in year 1 did not show statistically significant differences in frequency (7.6% vs. 7.3%; p = 0.98); however, a significant increase in the prevalence of AUD was observed between the first and second years after surgery (7.3% vs. 9.6%, p = 0.01); with greater likelihood AUD increase post-surgery independently related to RYGB, but not to restrictive procedures. A large-scale study from Sweden [13] documented that patients who have undergone RYGB surgery have a twofold-increased risk of inpatient care for alcohol abuse than those who have undergone restrictive bariatric surgery. Kalarchian et al used a structured clinical interview (n = 207) to diagnose AUD.…”
Section: Introductionmentioning
confidence: 99%
“…RYGB has been reported to cause more rapid and enhanced absorption of alcohol resulting in a faster rise and higher peak blood alcohol concentrations [6][7][8]. In a retrospective population-based cohort study, Östlund et al found that gastric bypass patients postoperatively used more inpatient care for alcohol-related disease compared with patients operated with gastric band or vertical banded gastroplasty [9]. In another prospective cohort study of RYGB patients, the presence of alcohol use disorders increased in the second postoperative year compared to the year prior to surgery [10].…”
Section: Introductionmentioning
confidence: 99%
“…There is strong evidence to suggest that alcohol addiction may be a significant potential complication after gastric bypass surgery in some patients [ 51 ]. King's and other studies have shown increased alcohol and other drug misuse and dependency in obese bariatric surgery patients [ 51 , 52 ], particularly after gastric bypass surgery [ 53 ].…”
Section: Introductionmentioning
confidence: 99%